Conservative Management of Paediatric Clavicle Fractures - Barry J. O'Neill; Alan P. Molloy; William Curtin (International Journal of Pediatrics)
Paediatric clavicle fractures have traditionally been treated nonoperatively. Recent studies have recommended operative management for displaced midshaft fractures. We conducted a retrospective review of all clavicle fractures in children aged one to sixteen over a two-year period. We classified fractures and evaluated followup and clinical outcome. We identified 190 fractures. There were 135 boys and 55 girls. 65% of fractures were displaced and 35% undisplaced. Mean radiographic and clinical followup was 35 days and 44 days, respectively. Clavicle fractures in children heal with nonoperative management. Radiographs of clavicle fractures in children are unnecessary in the absence of clinical symptoms.